(untitled) (Asian Business Research, 2017)
Securities issuance audit system is the most basic system of a country’s securities market, other systems play the role of ensuring its operation smoothly. The Third Plenary Session of the Eighteenth Central Committee of the Communist Party of China has established the registration system of stock issuance as the reform target. The registration system, that most mature markets used, can make up for the shortage of approval system of China’s stock issuance audit system at present. However, the registration system also has a higher realization of the foundation. This paper analyzes the shortcomings of the stock issuance under the approval system, discusses the basis of the implementation of the registration system, and puts forward some suggestions for reference from the functions of the CSRC, the qualities of investors and the supporting system of stock issuance.